Differences in eating habits between women with healthy pregnancy and those with preeclampsia - Guerrero-Cedillo, Mirtea Sagrario (Universidad de Sonora, 2023)
Introduction: In pregnancy it is of utmost importance to have healthy eating habits because these can considerably reduce the risk of overweight, obesity, cardiovascular diseases and hypertensive disorders such as preeclampsia and eclampsia. Objective: To determine the differences in the eating habits of women with healthy pregnancies compared to those who developed preeclampsia. Methodology: This is a descriptive comparative study in 100 women, using non-probabilistic sampling, considering 50 women with healthy pregnancy, 50 women who developed preeclampsia, and all with 18 years of age or older, no pregnant woman was excluded. The Encuesta Nutricional en Situación de Embarazo (Pregnancy Nutritional Survey (Pregnancy Nutritional Survey) was applied. The ethical aspects of research were observed in accordance with the Helsinki declaration. Group differences were analyzed with Pearson's chi-square test. Results: The mean age of the participants was 25.2 years; 68% had elementary school education, the pregestational weight reported was 69.8 kg and the gestational weight during pregnancy was 81.1 kg. There were statistically significant differences in current health perception, eating habits (consumption of fish, fruits, nuts, bread, rice or pasta and desserts), and dietary supplementation (multivitamins and minerals) in pregnant women who had a healthy pregnancy compared to those who developed preeclampsia. Conclusions: Eating habits during pregnancy are important, women with a healthy pregnancy have a different diet than those who developed preeclampsia, indicating that it is necessary to promote healthy eating since the first contact with the pregnant woman.